THE AUTHORITY AND ROLE OF THE REGIONAL HOUSE OF REPRESENTATIVES IN REALIZING CLEAN GOVERNMENT OFFICIALS IN THE ERA OF REGIONAL AUTONOMY - Amos Harita; Tamaulina Br. Sembiring; Ali Yusran Gea (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Constitution of the Republic of Indonesia Year 1945 regulates the House of Representatives (DPR) and regional autonomous government. Articles 18 to 18B of the 1945 Constitution discuss the division of regions and the regional government system, and Articles 19 and 20 of the 1945 Constitution regulate the DPR. In Indonesia, the House of Representatives is a state institution representing the people tasked with carrying out legislative, budgeting, and oversight functions over the performance of the government. In relation to local governments, the Regional House of Representatives (DPRD) and the local government are equal partners in administering regional governance, where the DPRD has the primary functions of legislation (enacting regional regulations), budgeting (preparing and approving the regional budget), and supervision (overseeing the implementation of regional regulations and local government policies), while the local government (led by the Head of the Region) has the function of executing regional regulations and local policies. They work together synergistically, with open communication, to ensure that development policies and programs meet the needs of the community and are implemented effectively and accountably. With the problem formulation being what are the inhibiting factors faced by the Regional House of Representatives (DPRD) in realizing a clean government apparatus in the era of regional autonomy. The purpose of this research is to identify the inhibiting factors faced by the DPRD in realizing a clean government apparatus in the era of regional autonomy. The benefits of the research include academic benefits, theoretical benefits, and practical benefits. The research methods consist of: type of research, nature of research, approach method, data sources (primary legal materials and secondary legal materials), data collection techniques, and data analysis methods. That based on the research results, the Regional House of Representatives (DPRD) is not performing its duties optimally due to limitations in human resource quality, lack of knowledge about regulations, procedures, and policies, as well as insufficient DPRD studies and a lack of intention to realize a clean government.